2017
DOI: 10.1103/physrevlett.118.158101
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Paradigm for Solution Demixing Inspired by Nuclear Transport in Living Cells

Abstract: Living cells display a remarkable capacity to compartmentalize their functional biochemistry. A particularly fascinating example is the cell nucleus. Exchange of macromolecules between the nucleus and the surrounding cytoplasm does not involve traversing a lipid bilayer membrane. Instead, large protein channels known as nuclear pores cross the nuclear envelope and regulate the passage of other proteins and RNA molecules. Beyond simply gating diffusion, the system of nuclear pores and associated transport recep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…[335,339,344,345] Similar uncertainty remains on how the relative concentrations of cargo in nucleus and cytoplasm depend on the numbers of transport proteins, Ran, RanGAP/GEF and various other adaptor proteins in the cell. Timney et al [86] found that the nucleo-cytoplasmic concentration ratio increases with cytoplasmic concentration of the transport proteins, while Elbaum and coworkers predict a non-monotonic function of the transport protein concentration [342,345]. Finally, [87,337] observed that the import rate is decreasing with the concentration of Importin-β (due to the depletion of RanGTP), although the connection between the initial accumulation rate and the relative concentrations at saturation is nontrivial [87,337].…”
Section: Nucleo-cytoplasmic Transport Cycle As a Pumpmentioning
confidence: 99%
See 2 more Smart Citations
“…[335,339,344,345] Similar uncertainty remains on how the relative concentrations of cargo in nucleus and cytoplasm depend on the numbers of transport proteins, Ran, RanGAP/GEF and various other adaptor proteins in the cell. Timney et al [86] found that the nucleo-cytoplasmic concentration ratio increases with cytoplasmic concentration of the transport proteins, while Elbaum and coworkers predict a non-monotonic function of the transport protein concentration [342,345]. Finally, [87,337] observed that the import rate is decreasing with the concentration of Importin-β (due to the depletion of RanGTP), although the connection between the initial accumulation rate and the relative concentrations at saturation is nontrivial [87,337].…”
Section: Nucleo-cytoplasmic Transport Cycle As a Pumpmentioning
confidence: 99%
“…Given the low efficiency of the transport cycle, it is possible that the import-export system is simply hitch-hiking on the RanGTP/GDP de-mixing cycle, which has other important roles, such as nucleosome positioning during cell division [335,340], and therefore is not necessarily optimized to facilitate cargo de-mixing between the nucleus and the cytoplasm. This point of view, which defines the ''futile cycle'' [341] of RanGTP/RanGDP conversion as a primary driver of the nucleocytoplasmic transport cycle, has been useful in conceptualizing the principles of nucleocytoplasmic de-mixing using the methods of non-equilibrium thermodynamics [342].…”
Section: Nucleo-cytoplasmic Transport Cycle As a Pumpmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopically, NPCs can efficiently import and export macromolecular cargoes into and out of the nucleus against the cargoes' apparent concentration gradients. From the thermodynamic standpoint, this requires energy input, which is provided by GTP hydrolysis during the transport cycle (4,22). In many other types of transporters (such as ion exchangers or proton pumps), GTP/ATP hydrolysis is directly coupled to directional substrate transport via conformational changes of the transporter (1,23).…”
Section: Simple Biophysics Of the Npcmentioning
confidence: 99%
“…In the nucleus, RanGDP is converted to RanGTP by a chromatin-associated guanine exchange factor RanGEF. Overall, directional transport is driven by the energy released from irreversible GTP hydrolysis in the cytoplasm (22) and maintained by the localization gradient of RanGTP; RanGTP concentration is higher in the nucleus relative to the cytoplasm. In turn, this gradient relies on the constitutive localizations of RanGEF in the nucleus, RanGAP1 in the cytoplasm, and the NTF2mediated transport of RanGDP (4).…”
Section: Simple Biophysics Of the Npcmentioning
confidence: 99%